Improving impact toughness of a high chromium cast iron regarding joint additive of nitrogen and titanium. (15th January 2016) - Ding, Hongsheng; Liu, Shiqiu; Zhang, Hailong; Guo, Jingjie
Abstract: In this work, the effect of nitrogen on the as-cast microstructure and impact toughness of high chromium cast irons(HCCIs) mainly containing 2.2%C, 25.0%Cr and 0.8%Ti was studied (all compositions are in wt.% in this work). The experimental results showed that with the addition of N(0.028%, 0.075%, 0.2%, respectively), Ti(C, N) precipitates were formed in the high chromium cast irons, and dispersedly distributed in M7 C3 carbides and austenite matrix. With the increase of nitrogen content, the microstructure was significantly refined, especially the M7 C3 carbides, which was related to the heterogeneous nucleation of M7 C3 carbide where Ti(C, N) precipitates act as the heterogeneous nuclei substrates. The Rockwell hardness of the specimen with 0.2% nitrogen increased to 49HRC in comparison to the specimen with 0.028% nitrogen (47HRC). The impact toughness of the specimen reached its peak value of 20.79 J/cm 2 with 0.075% nitrogen, improving almost 80% compared with the specimen with 0.028% nitrogen (11.80 J/cm 2 ). Graphical abstract: Highlights: Nitrogen refines M7 C3 carbides in high chromium cast iron. Ti(C, N) precipitates were identified in high chromium cast iron with joint addition of Ti and N. Ti(C, N) precipitates can act as the heterogeneous nuclei substrate for M7 C3 carbides. Impact toughness was improved with increasing nitrogen content.